Risk Factors of Pneumonia in Children A Community Survey (TAJ: Journal of Teachers Association, 2009)
Pneumonia was the leading common cause of death in young children in Bangladesh. 351 patients of Pneumonia below five years of age were selected as per WHO guidelines. Out of 351 patients, one patient died due to very severe pneumonia that had history of low birth weight and malnutrition. The following factors were taken into consideration such as age, sex, low birth weight, feeding pattern, malnutrition, housing, paternal education, ventilation of living room and smoking habits of parents. It was found that below 2 months of age, severe pneumonia showed 50% and there was male preponderance in all age group and also 41.6% of male children had recurrent attack of pneumonia. Low birth weight and lack of breast feeding patient had suffered more frequently of Pneumonia. In this study, it was statistically proved that malnutrition (p=.00028), inadequate paternal education (p=.00007), bad ventilated living room (p=.00037) and also smoking habits of parents (p=.04054) had significant important risk factors of recurrent attack of Pneumonia in children. doi: 10.3329/taj.v20i2.3072 TAJ 2007; 20(2): 122-126